Toxic Effects of Biogenic and Synthesized Silver Nanoparticles on Sea Urchin Echinometra lucunter Embryos - Bruni, Mariana [UNESP]; Ottoni, Cristiane [UNESP]; Abessa, Denis [UNESP] (Springer Nature, 2024)
Due to their broad-spectrum antimicrobial action and ease of synthesis, silver nanoparticles (AgNP) are one of the most widely used nanomaterials in different industrial and ecological areas. AgNP are released into marine ecosystems, nevertheless, their ecotoxicological effects have been overlooked. In this study, we evaluated the toxic effects of biogenic and synthesized AgNP (AgNPIBCLP11 and AgNPSINT) on sea urchin Echinometra lucunter embryos and compared them with the metal precursor silver nitrate (AgNO3). Fertilized eggs were exposed to five concentrations of the test compounds and a negative control for 48 h under controlled conditions. The IC50-48 h of AgNPIBCLP11, AgNPSINT and AgNO3 were 0.31, 4.095, and 0.01 µg L-1, evidencing that both AgNP are less toxic than AgNO3, and that AgNPSINT is less toxic than the AgNPIBCLP11. Toxicity to E. lucunter embryos could be explained by the fact that Ag affects DNA replication and induces the formation of pores in the cellular wall, leading to apoptosis.
Keywords: Biogenic silver nanoparticles; Echinometra lucunter; Marine environmental impact; Toxicity